Functional tricuspid regurgitation and recurrent admissions in patients with acute heart failure. (15th September 2019) - De la Espriella, Rafael; Santas, Enrique; Chorro, Francisco J.; Miñana, Gema; Soler, Meritxell; Bodí, Vicent; Valero, Ernesto; Núñez, Eduardo; Bayés-Genis, Antoni; Lupón, Josep; Sanchis, Juan; Núñez, Julio
Abstract: Background: Functional tricuspid regurgitation (TR) is a common echocardiographic finding in patients with heart failure (HF), and its role in disease progression and prognosis stratification is becoming increasingly relevant in recent years. However, data regarding its association with the burden of HF-readmission is scarce. In this work, we sought to evaluate the association between TR severity and HF-related readmissions following a hospitalization for acute heart failure (AHF). Methods: We prospectively included a cohort of 2101 patients admitted with the diagnosis of AHF. TR severity was assessed using a multiparametric integrative approach, and classified as none, mild, moderate, and severe. We used negative binomial regression to identify the association between TR grade and HF-related recurrent admissions. The risk associated to severity of TR was expressed as incidence rate ratio (IRR). Results: At a median follow-up of 2.53 years (IQR: 1.03–4.36), 978 (46.5%) patients died, and 1657 HF-readmissions occurred in 842 patients (40.0%). The proportion of patients with two or more admissions was 18.4%. The proportion of patients with moderate to severe TR was 17.2%. There was a stepwise increase in the incidence of readmissions from none to severe TR. After multivariable adjustment, only patients with severe TR were independently associated with higher risk of recurrent HF admissions (IRR = 1.34, CI 95%: 1.05–1.71; p = .019). Conclusions: In patients with AHF, severe functional TR is independently associated with an increased risk of long-term recurrent HF hospitalizations. Highlights: Functional tricuspid regurgitation (TR) is a common echocardiographic finding in patients with heart failure (HF). Recurrent HF-hospitalizations due to worsening HF negatively impact patient's outcome. The presence of severe TR before discharge is associated with an increased risk of recurrent HF-hospitalizations.